Socioenvironmental sustainability actions in hotel management - Lopes, Anderson Soares; Almeida, Paulo Santos de (Revista Brasileira de Ecoturismo (RBEcotur), 2018)
The present study contemplates an exploratory research of a qualitative nature in articles and sites, mainly associated to the tourism and Socioenvironmental sustainability aspects. Therefore, the main objective of this research is to identify and evaluate the actions of responsibility developed in the Socioenvironmental sphere by the employees of the hotel sector. In the midst of these considerations, it was used as a reference model Atlantica Hotels International and it is presented a diagnostic analysis in order to demonstrate through an applied research with the Training Manager and the organization's website in order to develop actions in the social and environmental context. In this way, there are opportunities to improve the environment which the lodging environment is located, aiming to preserve environmental resources, and to fight possible damages that may be caused by tourism, among this violence against children and adolescents..Ações de sustentabilidade socioambiental na hotelariaRESUMOO presente estudo contempla pesquisa exploratória de caráter qualitativo em artigos e sites, sobretudo, associadas as vertentes do turismo e da sustentabilidade socioambiental. Por isso o principal objetivo desta pesquisa é identificar e avaliar as ações de responsabilidade desenvolvidas na esfera socioambiental pelos colaboradores do setor hoteleiro. Em meio a estas considerações, utilizou-se como modelo referencial a Atlantica Hotels International e apresenta-se análise diagnóstica no intuito de demonstrar por meio de pesquisa aplicada com o Gestor de Treinamento e site desta organização formas de desenvolver ações no contexto social e ambiental. Desta maneira registram-se oportunidades para melhora do entorno em que o meio de hospedagem encontra-se inserido, com vistas a preservação dos recursos ambientais, e a combater possíveis danos que possam vir a ser causados pela atividade turística, dentre estes violências contra crianças e adolescentes.PALAVRAS-CHAVE: Turismo; Hotelaria; Sustentabilidade Socioambiental; Cidades Sustentáveis; Atlantica Hotels International.